GAMBARAN KINERJA PENGELOLA DI PUSKESMAS KOTA JAMBI - Andy Brata; Haflin Haflin (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2020)
Background: Pharmaceutical services at this time have changed their paradigm from drug to patients orientation, which refers to pharmaceutical care. As a consequence, pharmacists are required to improve their knowledge, skills and behavior so that they can interact directly with patients. Pharmaceutical services include the management of pharmaceutical preparations and medical consumables and clinical pharmacy services by utilizing personnel, funds, infrastructure, facilities and appropriate management methods in an effort to achieve the stated goals. The purpose of the study was conducted to determine the performance of drug managers in Jambi City Health Center according to Public Health Centre No. criteria. 74 of 2016. Method: The type of research used was explanatory research, conducted on drug management officers who work at the Jambi City Health Center. The sample was determined 20 drug management officers, selected by total sampling. Data was collected by distributing questionnaires to assess the performance of drug management officers on drug management at the Public Health Centre in Jambi City. The research variable was the performance of the drug manager in the Public Health Centre, the indicators of which are years of service, the commitment of the leaders, the knowledge possessed by the drug manager. The data then analyzed using Multiple Linear Regression technique. Results: The study showed that simultaneously the three dimensions of drug management had a significant effect on the performance of drug management; while partially one variable (leader commitment) has a significant effect (p <0.05), while the tenure and knowledge variables do not have a significant effect. The performance of drug management in the Jambi City Health Center is not affected by the years of service and knowledge of drug management officers. Conclusion: The performance of drug management was influenced by the commitment of the leader.